The Validity of Context-Based E-modules on Straight Motion Material to Improve the Critical Thinking Skills of High School Students - Larasati br Ginting, Putri Zulvia; Desnita, Desnita; Festiyed, Festiyed; Darvina, Yenni (Universitas Negeri Padang, 2025)
Critical Thinking is one of the important components in the independent curriculum Critical thinking is essential because it allows us to analyze, assess, and evaluate information, as well as make informed and logical decisions. One way to improve students' critical thinking skills is to use teaching materials. One of the teaching materials that is expected to overcome this problem is an E-Module based on a contextual approach to Straight Motion material to improve students' critical thinking skills. The type of research used in this study is Research and Development (R&D) research with a 4D development model. In this report, the results of the research are presented at the define, design, and develop stages. At the definition stage, observations were made to several schools. In the design stage, the design of the CTL integrated e-module framework was carried out. At the development stage, validation tests and practicality tests are carried out on the products that have been developed. The data instruments used in this study were questionnaires for teachers and students, validity test sheets and practicality test sheets. The data analysis techniques used are product validity analysis using Aiken’s V and product practicality analysis. A validity value of 0.90 was obtained with valid criteria. It can be concluded that the E-Module with a contextual approach to Straight Motion material to improve students' critical thinking skills developed is valid.